Pengembangan Potensi Desa Wisata Di Desa Kedungpane Kecamatan Mijen - Pranoto Pranoto; Lintang Jati Maharani; Abdul Kholiq; Muhamad Alifil Ma'luf; Anastasya Alya Ardhiningrum; Ahmad Zidane Alwi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2022)
Indonesia is a country that has a lot of potential in the tourism aspect. In its development, tourism involves other sectors such as agriculture, transportation, trade and industrial services and other sectors. So that it can be used as tourism for local residents and outside the village which at the same time can provide benefits for the village. Tourism village is basically an alternative to accommodate the needs of tourists who have special interests, and in fact, tourist villages have been in great demand by tourists, most of whom live in urban areas. As for tourists, the development of tourist villages is expected to support the diversification of tourism products that will enhance their travel experience. In this study the authors used a qualitative method. Qualitative research methods are often referred to as naturalistic research methods because the research is carried out in natural conditions.